The genomic response to 20-hydroxyecdysone at the onset of Drosophila metamorphosis. - Beckstead, R.B.; Lam, G.; Thummel, C.S. (Genome Biology, 2005)
The steroid hormone 20-hydroxyecdysone (20E) triggers the major developmental transitions in Drosophila, including molting and metamorphosis, and provides a model system for defining the developmental and molecular mechanisms of steroid signaling. 20E acts via a heterodimer of two nuclear receptors, the ecdysone receptor (EcR) and Ultraspiracle, to directly regulate target gene transcription.Here we identify the genomic transcriptional response to 20E as well as those genes that are dependent on EcR for their proper regulation. We show that genes regulated by 20E, and dependent on EcR, account for many transcripts that are significantly up- or downregulated at puparium formation. We provide evidence that 20E and EcR participate in the regulation of genes involved in metabolism, stress, and immunity at the onset of metamorphosis. We also present an initial characterization of a 20E primary-response regulatory gene identified in this study, brain tumor (brat), showing that brat mutations lead to defects during metamorphosis and changes in the expression of key 20E-regulated genes.This study provides a genome-wide basis for understanding how 20E and its receptor control metamorphosis, as well as a foundation for functional genomic analysis of key regulatory genes in the 20E signaling pathway during insect development.